Methane Fermentation of Ferulate and Benzoate: Anaerobic Degradation Pathways - Grbić-Galić, D. (1985)
The anaerobic biodegradation of ferulate and benzoate in stabilized methanogenic consortia was examined in detail. Up to 99% of the ferulate and 98% of the benzoate were converted to carbon dioxide and methane. Methanogenesis was inhibited with 2-bromoethanesulfonic acid, which reduced the gas production and enhanced the buildup of intermediates. Use of high-performance liquid chromatography and two gas chromatographic procedures yielded identification of the following compounds: caffeate, p-hydroxycinnamate, cinnamate, phenylpropionate, phenylacetate, benzoate, and toluene during ferulate degradation; and benzene, cyclohexane, methylcyclohexane, cyclohexanecarboxylate, cyclohexanone, 1-methylcyclohexanone, pimelate, adipate, succinate, lactate, heptanoate, caproate, isocaproate, valerate, butyrate, isobutyrate, propionate, and acetate during the degradation of either benzoate or ferulate. Based on the identification of the above compounds, more complete reductive pathways for ferulate and benzoate are proposed.